Training to Submit Scientific Articles in Accredited National Journals - Afriansyah, Ekasatya Aldila; Luritawaty, Irena Puji; Puspitasari, Nitta; Sundayana, Rostina; Mulyadi, Redi; Hidayat, Asep; latifah, Yusi; Damayanti, Desi (Indonesian Journal of Community Empowerment (IJCE), 2023)
The teacher's ignorance of the publication of journal articles became the starting point for the problems to be solved so it became the theme raised in this training. The solution provided through this training is material and guidance from the presenters to all participants. The purpose of this training activity is to provide information about articles and journals, as well as the process of submitting articles to accredited national journals, as well as the scope of it to MTs teachers in Garut Regency in particular, and generally to all other participants. The training method used has five stages, including introduction, socialization, training, practice, and monitoring. The subjects of this training are all teachers who are collected in the MGMP MTs Garut Regency, as well as other participants who work as teachers, lecturers, or students on a national scale. The training activities were carried out in two sessions, including material presentation and practical skills. The results of the evaluation form regarding this training activity were very good, all questions received positive responses and answers from all participants. It seems that several teachers have committed to follow up this training activity by trying to write their findings in the form of articles and publish them in the designated accredited national journals. This training concludes that the insights and knowledge conveyed by the presenters in this training activity can open the eyes of all teachers to aspects of scientific publications that so far have never even been glimpsed by teachers.